Islamic Finance : the New Regulatory Challenge - Abdel Karim, Rifaat Ahmed; Archer, Simon (New York : Wiley, 2013)
From the world's foremost authorities on the subject, the number-one guide to Islamic finance revised and updated for a post-crisis world Because it is entirely equity-based, rather than credit-based, Islamic finance is immune to the speculative bubbles and runaway volatility typical of Western finance. Especially now, in the wake of the global financial crisis, this has made them increasingly attractive to institutional investors, asset managers and hedge funds in search of more stable alternatives to conventional financial products. With interest in Islamic finance swiftly spreading.
pt. 1. The nature of risks in Islamic banking -- pt. 2. Capital adequacy -- pt. 3. Securitisation and capital markets -- pt. 4. Corporate governance and human resources -- pt. 5. Conclusion.
Includes bibliographical references and index.
Print version record.
Keywords: Finance -- Islamic countries; Finance -- Religious aspects -- Islam; Banks and banking -- Islamic countries; Banks and banking -- Religious aspects -- Islam; BUSINESS & ECONOMICS -- Finance; BUSINESS & ECONOMICS -- Banks & Banking; Banks and banking; Banks and banking -- Religious aspects -- Islam; Finance; Finance -- Religious aspects -- Islam; Islamic countries; Electronic books